2021
DOI: 10.1002/anie.202113780
|View full text |Cite
|
Sign up to set email alerts
|

Geomimetic Hydrothermal Synthesis of Polyimide‐Based Covalent Organic Frameworks

Abstract: Despite its abundance, water is not widely used as a medium for organic reactions. However, under geothermal conditions, water exhibits unique physicochemical properties, such as viscosity and a dielectric constant, and the ionic product become similar to those of common organic solvents. We have synthesized highly crystalline polyimide‐based covalent organic frameworks (PICs) under geomimetic hydrothermal conditions. By exploiting triphenylene‐2,3,6,7,10,11‐hexacarboxylic acid in combination with various arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…(2) While in the supernatant of the alcohol containing reaction mixture imide and amic acid species could be detected, the supernatant of the water reaction mixture contained predominantly deprotonated pyromellitic acid and protonated amine linker molecules (Figures S7–S10). This indicates the formation of a monomer-salt intermediate in the COF formation reaction prior to polymerization, by protonation of the amine linker by the hydrolyzed PMDA as described previously. , We observed that this monomer-salt intermediate (Figure S11) dissolves in water and also in the water/n-alcohol mixtures during the heating process, and amorphous PI begins to precipitate thereafter. Thus, while water could serve as a good solvent for PMDA and the intermediate salt, enabling the primary diffuse polymerization, and enhances the reversibility of the equilibrium reaction (Le Chatelier’s principle), the alcohol could contribute to enhancing the solubility of the amine precursor, enabling exchange of the amine linker molecule from the precipitated amorphous network during the defect healing processes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(2) While in the supernatant of the alcohol containing reaction mixture imide and amic acid species could be detected, the supernatant of the water reaction mixture contained predominantly deprotonated pyromellitic acid and protonated amine linker molecules (Figures S7–S10). This indicates the formation of a monomer-salt intermediate in the COF formation reaction prior to polymerization, by protonation of the amine linker by the hydrolyzed PMDA as described previously. , We observed that this monomer-salt intermediate (Figure S11) dissolves in water and also in the water/n-alcohol mixtures during the heating process, and amorphous PI begins to precipitate thereafter. Thus, while water could serve as a good solvent for PMDA and the intermediate salt, enabling the primary diffuse polymerization, and enhances the reversibility of the equilibrium reaction (Le Chatelier’s principle), the alcohol could contribute to enhancing the solubility of the amine precursor, enabling exchange of the amine linker molecule from the precipitated amorphous network during the defect healing processes.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the imide polymerization itself seemed to occur in the presence of water as evident from the typical imide vibrational bands in the fourier transform infrared (FT-IR) spectra of the precipitate (Figure S1). We thus reasoned that crystallization may either be prevented by a lack of solubility of the amine precursor molecules and imide oligomers in water, hindering the growth of well oriented COF sheets, or the lack of polarity differences in the reaction mixture. Indeed, most COFs have been reported to form crystalline structures in two-solvent mixtures of varying polarity, e.g., mesitylene (ε = 2.4) and NMP (ε = 32) for imide-linked COFs .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations